Pravno-komparativni model kao alat za uporednopravnu analizu / Legal-Comparative Model as a Comparative Analysis Tool - Bubalo, Lana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The text is a review of a book: Comparing Legal Cultures (Poređenje pravnih kultura) by Sören Koch and Jørn Øyrehaugen Sunde (eds.), Comparing Legal Cultures, 2nd Revised Edition, Fagbokforlaget, Bergen, 2020.